Odontogenic myxoma of the maxilla: A report of a rare case and review on histogenetic and diagnostic concepts - Shah, Ajaz (Medknow Publications & Media Pvt Ltd, 2011)
Odontogenic myxoma (OM) is a rare and locally invasive benign neoplasm (comprising of 3-6% of all odontogenic tumors) found exclusively in the jaws. OM commonly occurs in the second and third decades, and the mandible is involved more commonly than the maxilla. The lesion often grows without symptoms and presents as a painless swelling. The radiographic features are variable, and the diagnosis is therefore not easy. This article presents a rare case of OM occurring in the maxilla of a 37-year-old female patient with a brief review of the pathogenesis, clinical, radiological, histopathological, ultrastructural and immunohistochemical characteristics of OM.